Efektivitas Program Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) untuk Pemberdayaan Masyarakat Miskin - Muntaha Mardhatillah (Journal of Education on Social Science (JESS), 2021)
BKKBN as an organizer of family empowerment of the government to create a program Families Economic Empowerment by forming a group container (UPPKS), which is in its implementation in the city of Padang Panjang still encountered a number of problems. The purpose of this research is to determine the level of program effectiveness (UPPKS) in empowering the poor in Padang Panjang city, here are also seen what obstacles are encountered during program implementation and what efforts can be made to overcome these obstacles. The method used in this research is mixed methods were used to measure the effectiveness of the UPPKS program using the model of evaluation CIPO by Stufflebeam, then to get deeper conclusions regarding the results of the study used qualitative methods through observation and interviews. The research findings indicate that the effectiveness program (UPPKS) for empowerment of the poor in Padang Panjang been effective with 70.55% good category. Although the implementation of the program UPPKS in accordance with existing procedures but has not been fully able to improve the welfare of its members. This can be seen with still found some constraints in implementation, obstacles encountered can be categorized into two forms of internal constraints and external constraints. Internal constraints such as: weak supervision of the program, the lack of capital coming from the government, coaching is not evenly distributed. External constraints such as: the use of aid funds is not maximized, the lack of creativity and innovation groups in finding and utilizing financial resources, delays in repayment of the loan. Efforts are made to overcome these obstacles is to involve family welfare III acted as a foster father in group, guidance, and constraints derived from program participants made efforts such as mentoring, conducting proactive system for members jammed in payments.